(untitled) (Al-Qamar, 2022)
Without knowledge a man cannot know that he is a man. Without knowledge there is no difference among man, animal and non-living beings. Islam gives a great emphasis on knowledge. Without knowledge a man cannot know even about Islam, God and the matters of the universe and living. No doubt Jean-Jacques Rousseau was a great philosopher, presented many theories about different subjects and topics. In his one thesis, he has objected the authenticity of knowledge. It was the need of time to analyses these objections from the teachings of Islam. So here it is done.